ADVERTISEMENT, LIFESTYLE AND PRODUCT QUALITY IN INFLUENCING PURCHASE DECISION OF XIAOMI SMARTPHONE IN SUKOHARJO - Bela Elmatiara; Bambang Mursito; Sudarwati Sudarwati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Changes occur in all fields including in the field of communication equipment, companies are always required to produce the latest products and the best innovations so that they are different from previous product and consumers want to buy them. The attractiveness of advertising that reminds and makes consumers interested in advertised products makes purchase demand increase, in addition to offering products through advertising the product must also meet the lifestyle of someone who wears it. In addition to the attractiveness of advertising and lifestyle, the quality ofathe product also greatly affects the product that will be launched to the public because the quality ofathe product will determine the price of the product. Researchers conducted this study toadetermine and explain the influenceaofaadvertisingaattractiveness,.lifestyle.andaproduct.qualityainainfluencingapurchasing.decisions for xiaomi smartphones.in Sukoharjo. This recearch uses descriptive quantitative research with the independent variables of ad attractiveness, lifestyle and product quality. The sample population used is the entire Sukoharjo community, especially xiaomi smartphone users with a population of 3,780 people and a sample or 100 respondents, in taking the sample using purposive sapling technique and for data colletion using a questionnaire or questionnaire method. Based on the results of multiple linier regression tests, this study proves that.the attractiveness.of advertising, lifestyle and product quality.have a significant.effect on.purchasing.decisions together. Keywords: Addractiveness of Ads, Lilestyle, Product Quality